Evaluation of wheat (Triticum aestivum) genotypes for higher yield and enhanced nitrogen use efficiency in Indo-Gangetic Plains - GAWDIYA, SANDEEP; KUMAR, DINESH; SHIVAY, Y S (The Indian Journal of Agricultural Sciences, 2023)
Extensive research has been conducted on various nitrogen (N) management approaches to fulfil the growing needs of cereals while enhancing the efficiency of agricultural resource utilization. Nevertheless, the intensive agricultural model continues to prioritize the achievement of high crop yields and improving nitrogen use efficiency (NUE) as opposing targets. The primary aim of this study was to investigate whether a corresponding increase in N application is necessary to achieve higher crop yields. The study evaluated the effects of 3 N treatments (N0, N75, and N150) on 10 wheat (Triticum aestivum L.) genotypes during 2020–21 and 2021–22 at research farm of ICAR-Indian Agricultural Research Institute, New Delhi. In both growing seasons, the highest grain yield (GY) of 5.3 t/ha, agronomic efficiency (AEN) of 28.7 kg grain/kg N, and partial factor productivity of applied N (PFPN) of 60.2 kg grain/kg N were obtained by the HD 3249 genotype, followed by HD 3117. The application of N75 and N150 increased grain yields by 72.3 and 142.6%, respectively, over N0. Significant relationships were observed between GY, PFPN and AEN at all N levels, and a decreasing trend was observed in both PFPN and AEN as the N application rate increased. The study results suggest that the adoption of genotype-specific nitrogen (N) rates could provide a mutually beneficial solution to meet the growing demand for food while improving NUE. Overall, based on GY and AEN, the research findings indicate that the genotypes HD 3249 and HD 3117 are efficient candidates for N use, with the potential for higher yields and NUE in the Indo-Gangetic plains of India.